The Hui Muslims in China - Mai, Jianjun (Indonesian Journal of Islamic History and Culture, 2024)
The Hui Muslim is the largest Muslim minority ethnic group in China. While global attention has largely focused on China’s Uygur Muslims, the Hui Muslims have remained relatively marginalized, resulting in prevalent misconceptions about their identity as native Chinese converts to Islam. This article seeks to correct these misconceptions by exploring the deep historical roots of the Hui Muslims. In doing so, the article aims to shed light on the development and evolution of this unique Muslim minority, emphasizing its distinctive ethnic identity within a prominently non-Muslim Chinese society.